Analysis of lateral soil displacements induced by synchronous grouting in large-diameter shield tunnelling: a case study - Sige Peng; Haobin Huang; Hong Pan; Guanyong Luo; Hong Cao (Scientific Reports)
Abstract Soil displacement during underground tunnel construction has become a focal concern in recent decades. Numerous seismic events have revealed that many large deformation of the ground surface was due to underground tunnel construction, especially for the large-diameter shield tunnelling. Evaluating the impact of shield tunneling on surrounding soil requires an in-depth analysis of the extent, magnitude, and primary zones of disturbance caused by synchronous grouting at the shield machine tail. This study, based on a case involving short-range, high-frequency field monitoring during large-diameter shield tunnel construction, presents an incremental displacement method and maximum incremental displacement method to assess the patterns of lateral horizontal soil displacements induced by synchronous grouting. Results indicate a V-shaped displacement distribution in the longitudinal direction, with the disturbance zone extending approximately 1D (equal to the shield’s outer diameter). The inclination angle of the boundary was observed to correlate with soil properties. In the lateral direction, disturbances were concentrated just above the tunnel shoulder, with a width of approximately 0.7D, shifting upward as the depth of overlying soil increased. The inclination angle transitioned from shallow to steep within a symmetrical disturbance zone across both sides of the tunnel. Additionally, similar displacement patterns were confirmed in other cases using the maximum incremental displacement method, with an analysis of deformation modes and underlying causes of lateral soil upward movement.